Mortality Related to Nonalcoholic Fatty Liver Disease Is Increasing in the United States - James M. Paik (Hepatology Communications, 2019)
Population‐level nonalcoholic fatty liver disease (NAFLD) death rate data are sparse. We described death rates for adults with NAFLD in the United States using mortality data from the National Vital Statistics System multiple‐cause mortality data (2007‐2016). Decedents who had NAFLD were identified by International Classification of Diseases (ICD) codes K75.81, K76.0, K74.0, K74.6, and K76.9. Among NAFLD decedents, cause‐specific deaths (e.g., cardiovascular disease [CVD], cirrhosis, hepatocellular carcinoma [HCC], non‐liver cancer, diabetes mellitus [DM]) were identified by underlying cause of death ICD‐10 codes. Trends were evaluated by average annual percentage change (AAPC) in age‐standardized death rate (ASDR) per 100,000 persons. Among the 25,129,960 decedents aged ≥20 years, 353,234 (1.4%) decedents had NAFLD (212,322 men; 260,765 non‐Hispanic whites, 32,868 non‐Hispanic blacks, 46,530 Hispanics, 5,025 non‐Hispanic American Indian or Alaska Natives [AIANs], 7,023 non‐Hispanic Asian or Pacific Islanders [APIs]), with a mean age at death of 64.47 ± 13.17 years. During the study period, the ASDR for NAFLD increased by 15% (12.94 to 14.90; AAPC, 1.98%; P < 0.001]), while women (AAPC, 2.99% vs. 1.16% men; P = 0.003), non‐Hispanic whites (AAPC, 2.48%), non‐Hispanic AIANs (AAPC, 2.31%), and Hispanics (AAPC, 0.74%) experienced the highest annual increases. Stable trends were noted for non‐Hispanic blacks and non‐Hispanic APIs. Among subgroups, Mexican (AAPC, 1.75%) and Asian Indians (AAPC, 6.94%) experienced annual increases. The top six underlying causes of death (155,894 cirrhosis, 38,444 CVD, 19,466 non‐liver cancer, 10,867 HCC, 8,113 DM, and 5,683 lung disease) accounted for 67.5% of NAFLD‐related deaths. For cause‐specific deaths, ASDR increased for HCC (AAPC, 3.82%), DM (AAPC, 2.23%), non‐liver cancer (AAPC, 2.14%), CVD (AAPC, 1.59%), and cirrhosis (AAPC, 0.96%). Conclusion: NAFLD‐related deaths in U.S. adults are increasing. Cirrhosis is the top cause‐specific death, followed by CVD. Women, non‐Hispanic whites, and non‐Hispanic AIANs (subgroups Mexicans and Asian Indians) experienced the highest increases in deaths. Policies addressing the societal burden of NAFLD are needed.